Characteristics of Teacher-Nominated Shy Students in Norwegian Elementary Schools. Issue 2 (15th March 2023) - Mjelve, Liv H.; Nyborg, Geir; Arnesen, Anne; Bjørnebekk, Gunnar; Crozier, W. Ray; Coplan, Robert J.
ABSTRACT: The present study explored variations in the characteristics of teacher-nominated shy students. Participants were N = 329 teachers from 303 elementary schools across Norway. Teachers were first asked to select a current (or previously taught) student who was considered "shy, " and then rated different aspects of this child's school adjustment. Among the results, teacher-nominated shy students were found to be a heterogeneous group, varying substantively across several domains of functioning at school. Teachers' descriptions of shy students functioning did not vary significantly as a function of school characteristics (class/school size), teacher characteristics (gender/age/experience), or student grade. However, overall, teachers rated shy male students as evidencing more adjustment difficulties than shy female students. Results are discussed in terms of implications for educational practice.